Analisis economico de la produccion de yuca - Pinstrup-Andersen, Per; Díaz, R.O. (International Center for Tropical Agriculture, 1977)
An economic analysis is made of cassava production in Colombia, based on yields obtained by farmers surveyed in 5 different regions. Yields tended to be greater as farm size increased, averaging 8 and 14 ton/ha in the best zone for small and large farmers, respectively. Av yield was estimated at 6.2 t/ha, which is lower than the official national av of 8 t. There were marked variations in prices received by the farmers from one zone to another, but farm size did not affect price. Costs varied, tending to be higher for large farms, but total costs per ton were lower. Data on land and production costs, as well as net income per zone, are given. The rate of return on capital investment tended to increase as farm size increased. (CIAT)